2010
DOI: 10.1177/0888406409360129
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Beliefs of Special Educators: The Relationships Among Collective Efficacy, Teacher Self-Efficacy, and Job Satisfaction

Abstract: In order to examine the relationship between reported levels of teacher self-efficacy, collective efficacy, and job satisfaction in special educators, teachers in one school district completed three surveys measuring these constructs. The results indicated that teacher self-efficacy had a direct effect on job satisfaction. It was further found that collective efficacy directly affected teacher self-efficacy but that it did not have a direct effect on job satisfaction. No significant differences were found in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 27 publications
4
78
2
7
Order By: Relevance
“…Viel-Ruma et al [21] found that t a significant relationship between job satisfaction and teacher self-efficacy. Furthermore, a significant relationship between teacher self-efficacy and collective efficacy was found.…”
Section: Teachers' Collective Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Viel-Ruma et al [21] found that t a significant relationship between job satisfaction and teacher self-efficacy. Furthermore, a significant relationship between teacher self-efficacy and collective efficacy was found.…”
Section: Teachers' Collective Efficacymentioning
confidence: 99%
“…Viel-Ruma et al [21] surveyed 104 special educators and found that teacher self-efficacy had a direct effect on job satisfaction. It was further found that collective efficacy directly affected teacher self efficacy but that it did not have a direct effect on job satisfaction.…”
Section: Teachers' Efficacymentioning
confidence: 99%
“…Finally, individuals' physical and emotional states can affect their self-efficacy beliefs. In this regard, self-efficacy of teachers is related to their feelings of competence in their classes (Marri, Ahn, Fletcher, Heng & Hatch, 2012), the quality of classroom teaching (Zee & Koomen, 2010), student behaviors, professional experience (Egyed & Short, 2006), job satisfaction (Viel-Ruma, Houchins, Jolivette & Benson, 2010) and accountability pressure (Ford, Sickle, Clark, Fazio-Brunson & Schween, 2014).…”
Section: Teacher Self-efficacymentioning
confidence: 99%
“…A análise dos objetivos dos estudos que fazem parte desta revisão sistemática revela que a eficácia coletiva docente foi investigada em conjunto com as seguintes variáveis: (a) desempenho acadêmico -refere-se ao aproveitamento escolar dos alunos em sistemas institucionais de avaliação (Lee, Zhang, & Yin, 2011); (b) autoeficácia -é a crença do professor na sua própria capacidade para exercer com eficácia a sua função (Viel-Ruma, Houchins, Jolivette, & Benson, 2010); (c) comportamento infantil -refere-se ao comportamento disciplinar dos alunos nas séries iniciais do Ensino Fundamental (Lee et al, 2011);(d) estresse no trabalho -aplica-se ao estresse decorrente da rotina escolar no cumprimento da docência (Klassen, 2010); (e) redes de colaboração de professores -são as redes sociais de apoio que se estabelecem no ambiente de trabalho (Moolenaar, Sleegers, & Daly, 2012);(f) dimensão cultural -referente as características culturais de coletivismo ou individualismo (Klassen, Foster, Rajani, & Bowman, 2009); (g) satisfação no trabalho -é o grau em que as pessoas gostam da função que realizam (Duffy & Lent, 2009); (h) confiança nos colegas -é a confiança que um indivíduo tem no seu grupo (Lee et al, 2011); (i) estados emocionais -refere-se às experiências emocionais dos professores no ambiente escolar que podem influenciar o comportamento futuro (Stephanou, 2013); (j) formação profissional -aplica-se a uma contínua capacitação dos professores, visando ao aprimoramento da prática docente (Lee et al, 2011); (k) liderança do diretor -refere-se às atitudes de liderança de diretores de escolas, visando contribuir para a melhoria do desempenho docente e discente (Kurt, Duyar, & Çalik, 2012) A Figura 2 indica, ainda, o número de artigos que investigou as diferentes variáveis em conjunto com a eficácia coletiva docente. Destaca-se que as categorias não são exclusivas de um único estudo, uma vez que um mesmo artigo pode ter investigado uma ou mais variáveis.…”
Section: Objetivos Dos Estudosunclassified
“…Na identificação dos instrumentos de coleta de dados para medir a eficácia coletiva docente, notou-se que a CE-Scale (longform), de Goddard et al (2000), foi a mais utilizada, sendo aplicada em quatro estudos (Kurt et al, 2012;McCoach & Colbert, 2010;Viel-Ruma et al, 2010;). Essa escala, tipo likert, mede as crenças de eficácia coletiva de professores através de 21 itens, em um contínuo de 1 a 6.…”
Section: Instrumento De Coleta De Dadosunclassified